Contact Lens Associated Bacterial Keratitis: Common Organisms, Antibiotic Therapy, and Global Resistance Trends: A Systematic Review - Hatami, Hossein; Ghaffari Jolfayi, Amir; Ebrahimi, Ali; Golmohammadi, Saeid; Zangiabadian, Moein; Nasiri, Mohammad Javad (Frontiers in Ophthalmology, 2021)
Introduction: Contact lens wearing has been increased globally during recent decades, which is one of the main risk factors for developing microbial keratitis. It can lead to corneal scarring and perforation or even endophthalmitis and visual loss if it remains untreated. Among bacterial, fungal, protozoal, and viral agents which can cause microbial keratitis, bacteria are the most common cause. Therefore in this study, we aim to find common causative bacteria, sensitivity, and resistance to antibiotics and the outcome of antibiotic therapy in contact lens-related bacterial keratitis. Methods: A systematic search was carried out in PubMed/Medline, EMBASE, and Web of Science for published studies and Medrxiv for preprints up to February 30, 2021, and May 14, 2021, respectively. A combination of the following keywords was used: “Infection,” “Corneal infection,” “Keratitis,” “Microbial keratitis,” and “Contact lens.” Also, we used the “Contact lenses” MeSH term. Results: Twenty-six articles were included. From 1991 to 2018, 2916 episodes of contact lens-related microbial keratitis) CLMK( with 1642 episodes of proven bacterial keratitis has been reviewed in these studies. Pseudomonas aeruginosa, Staphylococcus spp., and Serratia marcescens were the three most common bacteria isolated from samples of patients with contact lens-related bacterial keratitis. Overall, isolated bacteria were most sensitive to Fluoroquinolones and aminoglycosides, especially Ciprofloxacin and gentamicin respectively, and most resistant against penicillin, cephalosporins especially cephazolin and chloramphenicol. Almost all Patients responded well to antibiotic therapy, with some exceptions that needed further surgical interventions. Conclusion: Antibiotics are efficient for treating almost all patients with contact lens-related bacterial keratitis if they are appropriately chosen based on common germs in every geographical region and the sensitivity and resistance of these germs against them. In this regard, Pseudomonas aeruginosa is the most common causative germ of contact lens-associated bacterial keratitis all over the world and is almost full-sensitive to Ciprofloxacin. Because of some different results about sensitivity and resistance of germs against some antibiotics like gentamicin, vancomycin, and chloramphenicol in the middle-east region, especially Iran, more in vitro and clinical studies are suggested.